UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MODEL QUANTUM TEACHING PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS V SDN 200507 PADANGSIDIMPUAN - Nursyaidah Nursyaidah; Rahma Wati Matondang (DIRASATUL IBTIDAIYAH, 2022)
The background of this research stems from the results of interviews with teachers and students in class V SDN 200507 Padangsidimpuan about learning motivation. Some indicators of learning motivation have not been met in Indonesian lessons. One of the causes is the methods used by teachers have shortcomings in increasing learning motivation. The purpose of this study was to increase students' motivation with the quantum teaching model in learning Indonesian in class V at SDN 200507 Padangsidimpuan. This type of research is classroom action research. This research was conducted in two cycles. The data collection instruments in this study were questionnaires. The subjects of this study were the fifth grade students of SDN 200507 Padangsidimpuan, totaling 23 people. The results of the learning motivation questionnaire showed that the learning motivation in the fifth grade of SDN 200507 Padangsdimpuan in Indonesian subjects had increased. The average student learning motivation before learning using the quantum teaching model or pre-cycle is in the medium category, with an average score of 52.13. In the first cycle, the higher learning motivation is in the high category, with a score of 63.95. In the second cycle, learning motivation increased to a very high category with an average score of 68.86. Based on the research results, the quantum teaching learning model can increase learning motivation in learning Indonesian in class V SDN 200507 Padangsidimpuan. Keywords: Quantum Teaching, Learning Motivation, Indonesian.